PELUANG DAN TANTANGAN ASEAN MENUJU KOMUNITAS ASEAN 2015 - Elfia Farida (Faculty of Law, Universitas Diponegoro, 2012)
Abtract Cebu Declaration on the Acceleration of the Establishment of an ASEAN Community by 2015 is an acceleration instrument of the establishment of an ASEAN Community by 2015. This research purpose to describe, explain and analyze prospect and challenge toward ASEAN Community. The research method is used the juridical-normative. The data obtained qualitatively analysed to reveal the truth. The prospect of ASEAN create an ASEAN Political Security Community, ASEAN Economic Community and ASEAN Socio-Cultural Community 2015 are create a security and political stability in Southeast Asian and develop an early warning system to protect conflict escalation; turning the diversity that characterizes the region into opportunities for business complementation making ASEAN a more dynamic and stronger segment of the global supply chain; building a community of caring societies, managing the social impacts of economic integration, promoting environmental sustainability and promoting an ASEAN identity. The challenge toward ASEAN Community is ASEAN Way Principles still used to dispute settlement, crisis of providing food and energy, terrorism issues, infrastructure and increase non State Actors. Therefore, ASEAN soon will evaluate ASEAN Way Principles to keep existence, effective and credibility of ASEAN in the future and become people-centered organization. Keywords : Prospect, Challenge, ASEAN Community Abstrak Cebu Declaration on the Acceleration of the Establishment of an ASEAN Community by 2015 merupakan instrumen percepatan pembentukan Komunitas ASEAN 2015. Penelitian ini bertujuan untuk menggambarkan, menjelaskan dan menganalisis peluang dan tantangan ASEAN menuju Komunitas ASEAN. Metode penelitian yang digunakan adalah yuridis normatif. Data yang diperoleh dianalisis secara kualitatif untuk memperoleh kebenaran. Peluang ASEAN untuk mencapai Komunitas Politik Keamanan ASEAN, Komunitas Ekonomi ASEAN dan Komunitas Sosial Budaya ASEAN tahun 2015 adalah tercapainya stabilitas politik dan keamanan di Asia Tenggara dan mengembangkan sistem peringatan dini untuk mencegah konflik dan eskalasinya; pembentukan karakter regional sebagai peluang bisnis sehingga ASEAN akan lebih dinamis, kuat dan punya daya saing di tingkat global; membentuk suatu komunitas masyarakat, mengatur pengaruh sosial dari integrasi ekonomi, membangun lingkungan yang berkelanjutan dan mewujudkan satu identitas ASEAN. Tantangan menuju Komunitas ASEAN adalah masih diberlakukannya prinsip-prinsip ASEAN Way untuk penyelesaian sengketa, krisis pangan dan energi, isu terorisme, infrastruktur dan meningkatnya non State actors. Oleh karena itu ASEAN segera melakukan evaluasi atas prinsip-prinsip dalam ASEAN Way untuk menjaga eksistensi, efektivitas dan kredibilitas ASEAN di masa yang akan datang dan menjadi organisasi yang bertumpu pada masyarakat. Kata Kunci : Peluang, Tantangan, Komunitas ASEAN